(3QSGdI CadGWhf GdMcje Edi aQajQjhS aj MbjbI faj faj GdZe hGdge hGKHGJ GdRgO Yf SDGd cGf SJQefg Edjgs - (3GadGWhf GdMcjes
(3ChdgG (B:s
(3HSe Gddg Gdedc GdMb QO cJGHc GjOc Gddg HcQGeI GdJhajb s
(3BNQgG (B:s
(3hef SeY GdhYX hGdMceI Ke de jYed HgeG cGfG TGgOjf Ydjg hgh eLehY HgeG s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQGdcJH GdeUQjI (B((3CNdGb JjehQ (B290) s
Keywords: (3GdadSaI hGdefWbs